2016
DOI: 10.1021/acs.jmedchem.5b01835
|View full text |Cite
|
Sign up to set email alerts
|

Quadruplex Nucleic Acids as Novel Therapeutic Targets

Abstract: Quadruplex-forming sequences are widely prevalent in human and other genomes, including bacterial ones. These sequences are over-represented in eukaryotic telomeres, promoters, and 5' untranslated regions. They can form quadruplex structures, which may be transient in many situations in normal cells since they can be effectively resolved by helicase action. Mutated helicases in cancer cells are unable to unwind quadruplexes, which are impediments to transcription, translation, or replication, depending on thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
476
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 516 publications
(485 citation statements)
references
References 279 publications
(599 reference statements)
9
476
0
Order By: Relevance
“…36,37 A comprehensive review on drug targeting of G-quadruplexes has recently appeared. 38 In the case of BCL2 we have also shown that the i-motif found on the C-rich strand functions as the transcriptional activator by binding to hnRNP LL. 39,40 For the hTERT promoter we have previously shown, by various biochemical and biophysical experiments, that the silencer element consists of an unusually complex structure that forms end-to-end stacked G-quadruplex structures from 12 G-tracts ( Figure 1B).…”
Section: Introductionmentioning
confidence: 84%
“…36,37 A comprehensive review on drug targeting of G-quadruplexes has recently appeared. 38 In the case of BCL2 we have also shown that the i-motif found on the C-rich strand functions as the transcriptional activator by binding to hnRNP LL. 39,40 For the hTERT promoter we have previously shown, by various biochemical and biophysical experiments, that the silencer element consists of an unusually complex structure that forms end-to-end stacked G-quadruplex structures from 12 G-tracts ( Figure 1B).…”
Section: Introductionmentioning
confidence: 84%
“…It is a widely used approach to screen chemical libraries to identify potential selective ligands that bind to quadruplexes. 14 The results define the putative binding site and highlight atomistic interactions of the docked ligand to its receptor. This has been proven useful in understanding several biochemical processes.…”
Section: Automated Molecular Dockingmentioning
confidence: 91%
“…A wide range of small molecules have been reported that bind to quadruplexes and a large number of structure-activity relationships were derived (Fig. 2) 13,14,28 . The majority of these ligands share a common structural feature of a planar aromatic chromophore.…”
Section: Review Articlementioning
confidence: 99%
“…Identification of ligands that selectively bind to duplex, triplex, i-motif and G-quadruplex (G4) structures is an important and challenging goal of drug discovery (12,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). G4 structures, in particular, have emerged as promising therapeutic targets for anti-cancer therapies (13,18,(27)(28)(29)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). A major challenge is to identify compounds that bind specifically to one of the several possible G4 structures without binding to duplex DNA.…”
Section: Introductionmentioning
confidence: 99%
“…A major challenge is to identify compounds that bind specifically to one of the several possible G4 structures without binding to duplex DNA. Over the last decades, a number of ligands that bind G4 structures have been described (38,43). Unfortunately, none have successfully progressed completely through clinical trials to become useful drugs.…”
Section: Introductionmentioning
confidence: 99%